EXPLORING THE EFFECTIVENESS OF TEACHING THROUGH ONLINE PLATFORMS - Akhmadjonova, Diyora (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
With the rapid advancement of technology, online platforms have become a popular medium for delivering educational content. This research article aims to investigate the effectiveness of teaching through online platforms, examining its impact on student learning outcomes, engagement, and overall educational experience. By exploring various studies and analyzing their findings, this article provides insights into the advantages and challenges associated with online teaching, along with recommendations for educators to optimize the use of online platforms in their teaching practices.